The Tectonic Thinking and Strategies in Louis I. Kahn’s Art Museums - Chih-Ming Shih; Fang-Jar Liou (International Journal of Architectural Engineering Technology, 2016)
Through the use of tectonic form to integrate natural lighting and modern mechanical services into his art museum designs, Louis Kahn was able to give full expression to the spatial poetics of his tectonic thinking. By making a comparative examination of the literature and illustrations and presenting 3D models, we examine how, in the process of giving shape to space, Kahn was able to make the most of the inherent qualities of his materials to integrate the mechanical services into his three museums designs—the Yale University Art Gallery (1951–53); the Kimbell Art Museum (1966–72); and the Yale Center for British Art (1969–74)—while also making ample use of natural lighting. We then go on to investigate why Kahn adopted a design concept which used tectonic form and natural lighting to give expression to the inherent spatial characteristics of a museum. The results indicate that the architectural principle of complying with the structural form and order were the main factors influencing Kahn’s approach to integrating the mechanical services and natural light into these three designs. It was also found that Kahn’s pioneering use of passive natural lighting has had a significant impact on subsequent museum designs.